The Effect of Lipopolysaccharides from Salmonella enterica on the Size, Density, and Compressibility of Phospholipid Vesicles - Tamás Szabó; Zuzana Garaiová; Sopio Melikishvili; Marek Tatarko; Zsófia Keresztes; Tibor Hianik (Biomimetics)
The properties of the large unilamellar vesicles (LUVs) from 1,2-dimyristoyl-sn-glycero-3-phosphatidylcholine (DMPC), modified by lipopolysaccharides (LPS) from Salmonella enterica sv. Enteritidis, which mimics Gram-negative bacteria, were studied by various physical methods. LPS, in the range of 0/20/50 % w/w relative to the lipid, had a regulatory role in the structure of the LUVs toward the lower size, low polydispersity, and over-a-month size stability due to the lower negative zeta potential. The addition of LPS resulted in increased density, which determined the ultrasound velocity and the specific adiabatic compressibility. In a 0.5/1/2 mg/mL concentration range, the total lipid content did not significantly affect the size of LUVs and influenced the density-related attributes similarly to the LPS content. A positive correlation was found between temperature and vesicle size, and a negative correlation was found between temperature and density and compressibility—except for the anomaly behavior at 25 °C, around the melting point of DMPC.